A Phenomenological Inquiry into Political Marketing Dynamics in Indonesia's 2024 Presidential Election: The Case of Anies Baswedan's Campaign Narrative - Muchsin Al-Fikri; Vilma Dewi Anggraeni; Sandra Irawaty; Mohd Solahuddin Shahruddin (International Journal of Nusantara Islam, 2026)
This study aims to analyze the political marketing strategies implemented by the Anies Rasyid Baswedan and Abdul Muhaimin Iskandar (AMIN) ticket in the 2024 Presidential Election through a phenomenological approach. The research focuses on interpreting the experiences of political actors—including the supporting parties, campaign teams, and volunteers—in building a political narrative based on change and social justice. The phenomenological approach was chosen to explore the subjective meaning of the political communication process and campaign strategies that shape the candidate pair's image in the public eye. The results of the study indicate that the strategy of Segmenting, Targeting, and Positioning (STP) and the implementation of the Marketing Mix (product, promotion, price, and place) became the main foundation in shaping the public perception of the AMIN ticket. Political products that emphasize moral values, integrity, and support for the common people were promoted through digital strategies and a massive volunteer movement. These findings confirm that political marketing is not only an electoral instrument, but also a social communication process that builds moral legitimacy and public participation. This research provides a theoretical contribution to the development of political marketing studies in Indonesia, particularly in the context of participatory democracy that emphasizes ethics, transparency, and public trust.